Revealing the deeper structure of the end-glacial Pärvie fault system in northern Sweden by seismic reflection profiling - O. Ahmadi; C. Juhlin; M. Ask; B. Lund (Solid Earth, 2015)
A new seismic reflection survey for imaging deeper levels of the end-glacial Pärvie fault system in northern Sweden was acquired in June 2014. The Pärvie fault system hosts the largest fault scarp so far documented in northern Scandinavia, both in terms of its length and calculated magnitude of the earthquake that generated it. Present-day microearthquakes occur along the length of the fault scarp on the eastern side of the scarp, in general agreement with an east-dipping main fault. In the central section of the fault system, where there is a number of subsidiary faults east of the main Pärvie scarp, it has been unclear how the earthquakes relate to the structures mapped at the surface. A seismic profile across the Pärvie fault system acquired in 2007, with a mechanical hammer as a source, showed a good correlation between the surface mapped faults and moderate to steeply dipping reflections. The most pronounced reflectors could be mapped to about 3 km depth. In the new seismic survey, for deeper penetration an explosive source with a maximum charge size of 8.34 kg in 20 m deep shot holes was used. Reflectors can now be traced to deeper levels with the main 65° east-dipping fault interpreted as a weakly reflective structure. As in the previous profile, there is a strongly reflective 60° west-dipping structure present to the east of the main fault that can now be mapped to about 8 km depth. Extrapolations of the main and subsidiary faults converge at a depth of about 11.5 km, where current earthquake activity is concentrated, suggesting their intersection has created favorable conditions for seismic stress release. Based on the present and previous seismic reflection data, we propose potential locations for future boreholes for scientific drilling into the fault system. These boreholes will provide a better understanding of the reflective nature of the fault structures and stress fields along the faults at depth.